Analisis Rencana, Program, dan Organisasi Penjualan pada UMKM Kerupuk CV Sumber Berkah Melimpah di Desa Karangandong, Kecamatan Driyorejo, Kabupaten Gresik - Brilliancy, Inge (Seminar Nasional Manajemen, 2025)
This study aims to analyze the sales strategy, plans, programs, and organizational structure of Small Medium Enterprise’s (SME’s) Kerupuk CV Sumber Berkah Melimpah in Karangandong Village. The research method used in this study is qualitative case study with data collection techniques through observation and interviews. The result show that SME’s Kerupuk CV Sumber Berkah Melimpah applies a “hold” strategy to maintain sales. To optimize its sales strategy, this SME’s needs to design a more structured sales program, redesign the geographically base sales organizational structure, and add six sales staff to achieve the annual target.